2011
DOI: 10.1111/j.1440-1843.2011.02095.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary adenocarcinoma: A renewed entity in 2011

Abstract: Lung cancer, of which non-small-cell lung cancer comprises the majority, is the leading cause of cancer-related deaths in the United States and worldwide. Lung adenocarcinomas are a major subtype of non-small-cell lung cancers, are increasing in incidence globally in both males and females and in smokers and non-smokers, and are the cause for almost 50% of deaths attributable to lung cancer. Lung adenocarcinoma is a tumour with complex biology that we have recently started to understand with the advent of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 138 publications
(524 reference statements)
1
80
0
1
Order By: Relevance
“…Feminine sexuality, histological type of adenocarcinoma (Rosai, 2009;Yang, 2011;Couraud et al, 2012;Matteis et al, 2013), and low age (Zhou and Christiani, 2011) comprise a higher proportion of non-smokers with lung cancer. Furthermore, the incidence of adenocarcinoma in non-smokers is higher in Asian population (Rosai, 2009) particularly in women (Kadara et al, 2012). The histological type of lung cancer which consists of 4 major classes (Petersen, 2011) is of prime importance in determining the type of therapy and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Feminine sexuality, histological type of adenocarcinoma (Rosai, 2009;Yang, 2011;Couraud et al, 2012;Matteis et al, 2013), and low age (Zhou and Christiani, 2011) comprise a higher proportion of non-smokers with lung cancer. Furthermore, the incidence of adenocarcinoma in non-smokers is higher in Asian population (Rosai, 2009) particularly in women (Kadara et al, 2012). The histological type of lung cancer which consists of 4 major classes (Petersen, 2011) is of prime importance in determining the type of therapy and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is a common cause of cancer-associated mortality in men and women worldwide (1,2). Lung adenocarcinoma (LAC), which is classified as a non-small cell lung cancer (NSCLC), is a prevalent subtype, accounting for ~25% of lung cancers (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinoma (LAC), which is classified as a non-small cell lung cancer (NSCLC), is a prevalent subtype, accounting for ~25% of lung cancers (2,3). Cigarette smoke remains to be a major etiological risk factor for lung cancer (1,4); a previous study reported that an increase in the incidence of LAC was correlated with cigarette smoking (5).…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for 80% of all lung cancer diagnoses, with lung adenocarcinoma (AC) representing one of the most predominant histological types of NSCLC and accounting for 20-30% of all cases (1,2). The majority of patients with NSCLC are diagnosed in the late stage, when the tumor has become unresectable; therefore, chemotherapy remains the first treatment plan for advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%